Pengaruh Penggunaan Buku Cerita Bergambar Terhadap Kemampuan Berbicara Anak - Eka Mei Ratnasari; Enny Zubaidah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
The development of speaking ability for children is very important so that children could adapt and socialize with friends. This research aimed to determine the influence of picture book on children speaking ability aged of 4-5 years. The type of the research was quasi-experiment. The subjects of this study were the children of group A in Pringwulung kindergarten Yogyakarta, Indonesia. The data collection used an observation sheet, and then analyzed using the t-test through SPSS 16 program to see the differences in speaking ability between the two groups. The result of the research was that there is a significant influence on the improvement of children's speaking ability through picture book of preschool children in Pringwulung kindergarten Yogyakarta. The recommendations of this research can be used by teachers, parents, education practitioners in order to provide an optimal stimulation to the development of children's speaking ability.